MINERVA: A facility to study Microstructure and INterface Evolution in Realtime under VAcuum - Nicklin, C; Martinez Hardigree, J; Warne, A; Green, S; Burt, M; Naylor, J; Dorman, A; Wicks, D; Din, S; Riede, M (AIP Publishing, 2017)
A sample environment to enable real-time X-ray scattering measurements to be recorded during the growth of materials by thermal evaporation in vacuum is presented. The in-situ capabilities include studying microstructure development with time or during exposure to different environmental conditions, such as temperature and gas pressure. The chamber provides internal slits and a beam stop, to reduce the background scattering from the X-rays passing through the entrance and exit windows, together with highly controllable flux rates of the evaporants. Initial experiments demonstrate some of the possibilities by monitoring the growth of bathophenanthroline (BPhen), a common molecule used in organic solar cells and organic light emitting diodes, including the development of the microstructure with time and depth within the film. The results show how BPhen nanocrystal structures coarsen at room temperature under vacuum, highlighting the importance of using real time measurements to understand the as deposited pristine film structure and its development with time. More generally, this sample environment is versatile and can be used for investigation of structure-property relationships in a wide range of vacuum deposited materials and their applications in, for example, optoelectronic devices and energy storage.